2009
DOI: 10.1534/genetics.108.098434
|View full text |Cite
|
Sign up to set email alerts
|

The Ras/cAMP Pathway and the CDK-Like Kinase Ime2 Regulate the MAPK Smk1 and Spore Morphogenesis in Saccharomyces cerevisiae

Abstract: Meiotic development (sporulation) in the yeast Saccharomyces cerevisiae is induced by nutritional deprivation. Smk1 is a meiosis-specific MAP kinase homolog that controls spore morphogenesis after the meiotic divisions have taken place. In this study, recessive mutants that suppress the sporulation defect of a smk1-2 temperature-sensitive hypomorph were isolated. The suppressors are partial function alleles of CDC25 and CYR1, which encode the Ras GDP/GTP exchange factor and adenyl cyclase, respectively, and MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
(81 reference statements)
2
32
0
Order By: Relevance
“…Before commitment, a high level of PKA activity leads to the abandonment of meiosis and return to growth (53). However, measurements of cAMP levels during sporulation and mutational analyses of Ras/cAMP/PKA pathway components (33,61,62,64) have suggested that PKA is active during a longer period after meiotic entry. Moreover, a negative-feedback loop relying on the expression of BCY1 prevents very high levels of activity of PKA after commitment to meiosis (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before commitment, a high level of PKA activity leads to the abandonment of meiosis and return to growth (53). However, measurements of cAMP levels during sporulation and mutational analyses of Ras/cAMP/PKA pathway components (33,61,62,64) have suggested that PKA is active during a longer period after meiotic entry. Moreover, a negative-feedback loop relying on the expression of BCY1 prevents very high levels of activity of PKA after commitment to meiosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the expression of glucose-dependent PKA targets is not upregulated under these conditions (14). The last step in spore biogenesis, the synthesis of mature spore walls, has been found to be influenced by PKA activity via the activation of the meiosis-specific mitogen-activated protein (MAP) kinase homolog Smk1 (33).…”
mentioning
confidence: 99%
“…The cellular cAMP level is regulated by phosphodiesterase specific for its degradation in addition to adenylyl cyclase specific for its production (Sunahara and Taussig 2002;Houslay and Adams 2003). This cyclic nucleotide also participates in the control of cell cycle progression in the yeast Saccharomyces cerevisiae, as judged by its inhibitory activity on ascospore formation in response to nutrient starvation (McDonald et al 2009). It seems possible to find a substance that can elevate the intracellular cAMP level by applying simple microscopic observation of the yeast cell differentiation process.…”
mentioning
confidence: 99%
“…Although there are many possible explanations for these negative data, they do raise the possibility that additional regulatory features that are present only in meiotic cells promote the SSP2-dependent phosphorylation of Smk1. AMA1 and IME2 have been shown to promote Smk1 activation (20,37), and the role of these meiosis-specific genes in controlling the SSP2-dependent activation of Smk1 requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…AMA1, which encodes a meiosis-specific activator of the anaphase-promoting complex E3 ubiquitin-ligase (32)(33)(34)(35)(36), was also identified in the deletion mutant screen. In addition, Ime2 has been shown to increase the fraction of Smk1 that is phosphorylated (37).…”
mentioning
confidence: 99%